2016
DOI: 10.1007/s12070-016-0980-6
|View full text |Cite
|
Sign up to set email alerts
|

A New Predictor for Obstructive Sleep Apnea Syndrome: Monocyte to HDL Ratio

Abstract: The aim of this study was to investigate the relation of serum monocyte to serum HDL cholesterol ratio with obstructive sleep apnea syndrome (OSAS). A total of 336 patients who underwent polysomnography (PSG) were included in this study. The individuals with an apnea hypopnea index (AHI) <5/h were included in the study as controls while the patients with an AHI > 5 and excessive daytime sleepiness were included in the study as OSAS patients. OSAS patients were compared with the control group for serum monocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
6
11
0
Order By: Relevance
“…In our study, significantly higher MHR values were observed in patients with OSA when compared with the control group. The MHR values had a linear correlation with AHI, and the severity of hypoxemia defined by mean SpO 2 , LSpO 2 and TS90, which was consistent with previous studies (17,19). Furthermore, the levels of MHR were significantly higher in OSA patients with CVD, especially in severe OSA group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, significantly higher MHR values were observed in patients with OSA when compared with the control group. The MHR values had a linear correlation with AHI, and the severity of hypoxemia defined by mean SpO 2 , LSpO 2 and TS90, which was consistent with previous studies (17,19). Furthermore, the levels of MHR were significantly higher in OSA patients with CVD, especially in severe OSA group.…”
Section: Discussionsupporting
confidence: 90%
“…Recent study found significant increase of total monocyte in bone marrow and peripheral blood upon OSA related chronic intermittent hypoxia (CIH) exposure (15), and OSA severity was independently associated with low HDL-C values as well (16). Atan et al (17) reported MHR increased as OSA severity increased, which can be used as a new predictor for OSA. However, the association between MHR and CVD occurrence in patients with OSA still lacks clinical evidence and has not been well understood, especially in Chinese Han population.…”
Section: Original Articlementioning
confidence: 99%
“…As MHR is an inexpensive and readily available parameter, it has become more widely used in recent years, and has been related to several clinical conditions (13)(14)(15)(16). The relationship between OSAS and MHR was first investigated by Atan et al in 2007, and it was determined that MHR could be a predictive marker in OSAS diagnosis (17). In the present study, the value of MHR of the patients with OSAS was determined to be statistically significantly higher than that of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…is > 5 or the AHI is > 15 for an asymptomatic patient [1,2]. Recurrent nocturnal apnea episodes in OSAS patients cause sympathetic system activation, increased oxidative stress, endothelial dysfunction, sudden increase in systemic hypertension, hypoxia and hypercapnia [3].…”
mentioning
confidence: 99%
“…There was a positive correlation between MHR and the severity of hypoxemia defined by oxygen desaturation index (ODI) [47]. MHR, AHI, rapid eye movement (REM) -AHI, non-REM-AHI and oxygen saturation have been shown to increase significantly as time increases below 90% and the minimum oxygen concentration decreases [2] independently associated with corner atherosclerosis assessed by SYNTAX (Synergy Between Percutaneous Coronary Intervention With Taxus and Cardiac Surgery) score in patients with independent coronary artery disease. In addition, a positive correlation was found between CRP and MHR [48].…”
mentioning
confidence: 99%